Fire-Damaged Normal Concrete Properties And Bond Strength Evaluation Of Ultra High Performance Fibre Reinforced Concrete As A Repair Material - Baharuddin, Nur Khaida (2017)
It is well known that the mechanical properties of concrete structure deteriorate after exposure to fire. Repair and strengthening in order to improve the performance of the affected structure has become critical. Ultra High Performance Fibre Reinforced Concrete (UHPFRC) has been used as repair material due to its superior properties. The aim of this study is to evaluate mechanical and physical characteristic of normal concrete substrate subjected to different heating duration, to identify the most suitable substrate surface moisture condition in repairing fire-damaged concrete and to investigate the effect of substrate heating duration subjected to the bond strength and type of failure occur. Firstly, at the age of 28 days all normal concrete specimens were heated up. The temperatures are 600°C for 30, 60, 90, 120 and 150 minutes. The changes of Fire-damaged Normal Concrete (FDNC) in term of quality, mass, compressive strength and colour were examined. Several tests conducted to evaluate the properties of concrete after fires were Compressive Test, Rebound Hammer Test, Ultra-sonic Pulse Velocity Test, Initial Surface Absorption Test, Porosity and Water Absorption Test. Next, all the fire-damaged samples repaired with using UHPFRC. The substrate surface was sand blasted and moistened by three methods which are Air Dry (AD), Saturated Surface Dry (SSD) and Wet (WT). From this stage, the optimum moisture condition which gives highest bond strength was used in the next step. Then, the test to verify their bond strength namely Splitting Tensile Test, Slant Shear Test and Pull Off Test conducted. The result indicates that the substrate moisture condition influences FDNC bonding strength with UHPFRC. Based on the tests conducted, SSD condition is favourable while the substrate surface should not in dry state. With same degree of temperature, the heating durations give various degree of damaged on concrete. As the heating duration increase, normal concrete loss its compressive strength, tensile strength, stiffness and cracking occurred. The quality of concrete also reduced. Heating duration of normal concrete substrate, also affects their bonding strength with UHPFRC. These substrate damages surely give negative effects to their bonding strength with UHPFRC. Most of the failure occurs in the tests are through the FDNC substrate. The most frequent failure mode occurred was the failure at the interface with minor substrate crushing. It is indicated that the substrate strength was lower than the bond strength.